Les Souffleurs d’images - Joan Despéramont (Les Cahiers de l'École du Louvre)
The Souffleurs d’Images programme was developed by the Centre Recherche Théâtre Handicap in 2008 to make the performing arts accessible to the visually impaired students of its drama school, Acte 21. The principle is simple: a drama, circus arts, applied arts or art history student accompanies a visually impaired person to the cultural event of his or her choice (play, circus, exhibition, etc.) to whisper about the elements that he or she cannot see. Entirely free of charge and personalised, this service has many benefits, which will be presented in this article.